2012
DOI: 10.2139/ssrn.2161803
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Containment Policies in Public Pharmaceutical Spending in the EU

Abstract: This paper presents and evaluates pharmaceutical policies in the EU aimed at the rational use of medicines and at keeping pharmaceutical spending under control. Policy makers are growing more aware that by regulating pharmaceutical markets correctly, considerable savings can be achieved without compromising the quality of care. Specifically, the paper makes the case that, by following numerous best-practices in pharmaceutical sector regulations, the value for money of pharmaceutical consumption could be substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
171
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(171 citation statements)
references
References 34 publications
0
171
0
Order By: Relevance
“…On the contrary, countries with high purchasing power had lower PPP-adjusted prices rendering higher affordability and better access to innovative treatments [23]. In 2012, Carone et al noted in their report that drug prices adjusted using GDP per capita were higher in Poland, Romania, and Bulgaria as compared to Germany, Denmark, and Italy [25]. No study was found assessing the relative prices of orphan drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, countries with high purchasing power had lower PPP-adjusted prices rendering higher affordability and better access to innovative treatments [23]. In 2012, Carone et al noted in their report that drug prices adjusted using GDP per capita were higher in Poland, Romania, and Bulgaria as compared to Germany, Denmark, and Italy [25]. No study was found assessing the relative prices of orphan drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Price differentials based on purchasing power have repercussions. High price differences may lead to parallel imports from low-priced countries to higher-priced countries resulting in drug shortages in low-priced countries [25]. As such, similarity in absolute prices among neighbouring countries is a rational method to avoid such a scenario and thus ERP is continuously utilised by pharmaceutical companies in Europe to avoid parallel trade.…”
Section: Discussionmentioning
confidence: 99%
“…7 An exception is Danzon and Chao (2000), who argue that reference pricing might be counterproductive in curbing pharmaceutical expenditures. 8 pricing has a negative e¤ect on generic entry, whereas a recent study by Brekke et al (2015) on the Norwegian market …nd that reference pricing has a positive e¤ect on generic entry. Our paper suggests that the mixed empirical …ndings can be explained by the presence and strictness of price cap regulation.…”
Section: Introductionmentioning
confidence: 92%
“…4 However, only a few studies have considered the impact 1 See, for instance, Carone et al (2012) for an overview and a discussion of the recent development of costcontainment policies in the EU. 2 The Medicare Modernization Act in 2003 established a standard drug bene…t that all Medicare Part D plans must o¤er, which basically is a coinsurance scheme (with a deductible).…”
Section: Introductionmentioning
confidence: 99%